Weiblichkeit : Ansätze Zur Theoretisierung - Langer, Antje, 1973-; Mahs, Claudia; Rendtorff, Barbara (Jahrbuch Frauen- und Geschlechterforschung in der Erziehungswissenschaft series, 2018)
The volume aims to contribute to developing more differentiated approaches to the theoretical understanding of constructions of femininity. The contributions discuss various aspects such as discourses on femininity, analysis of 'hegemonic femininity', bridging to body-theoretical considerations, the tension between femininity and motherhood, and the role of corresponding attributions in educational or counseling settings.